Nonformal education for improving educational outcomes for street children and street youth in developing countries: A systematic review. (27th February 2014) - Shephard, Daniel D.
<x xml:space="preserve">Abstract</x> Tens of millions of children and youth (up to 24 years of age) live and work on the streets of developing countries. Most of them are forced to leave formal education. As a potential solution, nonformal education (NFE) interventions have spread worldwide. However, no previous attempt has been made to address the state of evidence regarding effectiveness studies of NFE for street children and youth. This review addresses this gap by conducting the first systematic review concerning the effectiveness of NFE for improving educational outcomes for street children and street youth. The search was conducted in 35 structured electronic databases and numerous organizations and experts were also contacted. The screening of 9, 271 titles resulted in the identification of zero prospective effectiveness studies with a counterfactual. Lessons are drawn from the highest quality excluded studies to inform future evaluations that seek to address this knowledge gap. Key Practitioner Message: ● Practitioners should implement comparable intake and monitoring assessments to track changes consistently over time; ● Programs informed by critical pedagogy and empowerment‐based approaches may improve behavioral outcomes; ● Programs that work with street children and street youth should clarify how they identify their target population.